Influencia del ph, concentración de coagulante y floculante en la remoción de sólidos suspendidos, demanda química de oxígeno y turbidez en efluente de lavado de pulpa de la planta papelera trupal s.a. - Carrera García, Grecia Del Rocío (2015)
The objective of this work was to evaluate the influence of pH, coagulant concentration and flocculant in the removal of suspended solids, Chemical Oxygen Demand and Turbidity in Effluent of Pulp Washing of the Plant Bin Trupal SA. was conducted this research. The evaluated variables were pH (in the range of 4-7), coagulant concentration and flocculant type, on which was determined after obtaining the pH at which the coagulant is best unfolds, on the dependent variables were chemical oxygen demand, Solid suspended, Turbidity, sludge volume and settling time. The most appropriate values of variables were determined by the method of test jars which allows to determine the optimal dose of coagulant and the optimum pH for coagulation. The best pH conditions for a good result in coagulation, is the original sample at a concentration of 700 ppm of “Policloruro de Aluminio” with 4 ppm of “Floculante cationico”; which it decreased by 98.94% Suspended Solids, 90.2% Chemical Oxygen Demand and 98.5% Turbidity of the effluent from the pulp washing Plant Bin Trupal S.A.